MODELING OF WHITE MISTLETOE POPULATION TO DECISION PROBLEMS OF ENVIRONMENTAL MANAGEMENT OF URBOECOSYSTEMS - and and (Municipal economy of cities. Series: «Economy science», 2016)
Тhe problem of the White Mistletoe (Viscum album L.) population control in urban landscape was studied to improve environmental management on urban areas. Field survey of mistletoe distribution was carried out in the city of Kharkiv (Ukraine). On the sampling areas of urban landscape the White Mistletoe was found on 18 tree species. The martix model of the White Mistletoe population dynamics was developed, the parameters of the model were determined according to data of field researches. Settings of the mode parameters conducted in two stages. The model allows to analyse changes over time in the number of mistletoe shrubs, their distribution by age as in retrospect and in the future. Vegetative propagation is substantiated to play a leading role in growth of mistletoe population. Keywords: mistletoe, model, population dynamics, environmental management, urban area.